The Implementation of Al-Qur’an Memorization Program at Golden Insan Madani Integrated Islamic Junior High School, Teluk Kayu Putih - Giantara, Haris (The Future of Education Journal, 2025)
The community service activities carried out by KKN (Community Service Program) students from Sekolah Tinggi Ilmu Tarbiyah Nahdatul Ulama (STITNU Sakinah) Dharmasraya from April 1st to 23rd, 2025, in Teluk Kayu Putih Village, VII Koto District, Tebo Regency, have provided significant benefits to the local community. The residents of Teluk Kayu Putih Village responded enthusiastically and positively to the socialization of the planned programs. These programs included: (1) Ramadan pesantren, (2) Ramadan outreach (turba), (3) subuh education activities, (4) distribution of iftar meals (takjil), (5) campus introduction/socialization, and (6) sub-district level competitions. The implementation of the subuh education and Ramadan outreach programs has contributed to improving the religious and educational quality among the children in the village.This study aims to analyze the implementation of Tahfidz Al-Qur’an learning at SMP Islam Terpadu Golden Insan Madani in Teluk Kayu Putih. The research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. The results show that the tahfidz program is conducted in a structured manner using  talaqqi (face-to-face recitation) method and memorization submissions, with regular evaluations. This program positively impacts students’ memorization ability and supports the development of Islamic character.